Tourist behavioral loyalty: a comparison of first-time and repeat tourist in the UNESCO World Heritage Site (WHS) in Malaysia - Ab Karim, Muhammad Shahrim; Leong, Quee Ling (Sinop: Mustafa Daşkın, 2019)
The present study aims to investigate the structural relationships among food involvement, food knowledge, food experience, food image, destination image, overall satisfaction and behavioral loyalty across first-time and repeat tourist groups from the perspective of food tourism. The study also examines if differences exist in these variables across the two groups of tourists. The „catch-as-catch-can‟ technique was used to sample international tourist in Melaka and George Town, Malaysia. A total of 1200 questionnaires were collected on-site and 75% of the total was randomly picked using SPSS, resulting in 868 responses analyzed. The two-step approach of structural equation modeling (SEM) was used to accomplish the study objectives. The t-test analysis demonstrated that repeat tourists expressed significantly higher food knowledge and behavioral loyalty than first-time tourists. The SEM results revealed that the structural model differed across first-time and repeat customers. This research contributes to the theoretical understanding of behavioral loyalty process across first-time and repeat tourists in the World Heritage Site (WHS) of Malaysia from the food perspective.